The distribution of IgG subclass deposition on renal tissues from patients with anti-glomerular basement membrane disease - Qu, Zhen (BioMed Central, 2013)
BACKGROUND: Renal injury of anti-glomerular basement membrane (GBM) disease is defined by the linear deposition of IgG along GBM and rapidly progressive glomerulonephritis. To date, the distribution of anti-GBM IgG subclasses on renal tissue is still unclear. In the current study, we investigated the deposition of the four IgG subclasses using immunohistochemistry in the renal biopsy specimens from 46 patients with anti-GBM disease. RESULTS: All four IgG subclasses can be detected within the GBM. Anti-GBM IgG3 was detected in all patients (100%), with 39 (84.8%) patients presenting with weak segmental staining and 7 (15.2%) patients with strong linear deposition. Anti-GBM IgG2 was detected in 22 (47.8%) patients, with 20 (90.9%) patients having weak segmental deposition and 2 (9.1%) patients presenting strong linear staining. Anti-GBM IgG1 and IgG4 were detected in 9 (19.6%) and 7 (15.2%) patients, respectively. IgG deposition along tubular basement membrane (TBM) was also detected in 31 (67.4%) patients. Among them, the IgG subclass distribution was similar to that of the deposition within the GBM: IgG1 6.5% (2/31), IgG2 45.2% (14/31), IgG3 100% (31/31) and IgG4 9.7% (3/31). We observed increased inflammatory cell infiltration into the interstitium in patients with increased anti-TBM IgG3 deposits (P=0.031). CONCLUSIONS: Anti-GBM IgG3 predominantly deposits along GBM and TBM on renal biopsy specimens from patients with anti-GBM disease, which may be involved in the development of renal injury of the disease.